(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper proposes the new architecture of overlay network of Distributed Hash table (DHT). We introduce a new MultiChord Protocol which is another variant of Chord Protocol defined over overlay network of Distributed Hash table. MultiChord inherits basic properties of Chord protocol with some added new features.